Early Diagnosis of Schizophrenia and Secondary Diagnose of Cerebral autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy: A Case Report - Farzaneh Modaresi; Mahboubeh Eslamzadeh; Aliasghar Karimi; Amir Ansari (Fasa University of Medical Sciences, 2022)
Background & Objective: Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) is a rare disease with a prevalence estimation of, 5 per, 100,000 individuals. Besides, it can highly be misdiagnosed with other psychiatric disorders. Case Presentation: We report a case of CADASIL in a 32-year-old Asian female presenting with schizophrenia symptoms such as auditory hallucination ،loosening of associations، persecutory delusions، referential delusions، decreased function, and complex hepatic hallucinations that the patient had said sometimes someone has intercourse with me since 2 years ago. After brain Magnetic Resonance Imaging (MRI) and gene checking, she showed up with NOTCH3 gene, besides Brain Magnetic resonance imaging confirmed the presence of CADASIL. Supportive treatments have been done and two years of following up showed a significant increase in patient life quality. Conclusion: This case report demonstrates the challenges of CADASIL diagnosis in a patient with schizophrenia symptoms. The diagnosis should be considered in patients with schizophrenia symptoms. Hence, there is a need for timely diagnosis and management of this disorder. Keywords: CADASIL, Brain Magnetic resonance imaging, NOTCH3 Gene, schizophrenia